2012
DOI: 10.1111/j.1530-0277.2012.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure, Attention‐Deficit/Hyperactivity Disorder, and Sluggish Cognitive Tempo

Abstract: Background Children with heavy prenatal alcohol exposure often meet criteria for attention-deficit/hyperactivity disorder (ADHD). ADHD research has examined subtype differences in symptomology, including sluggish cognitive tempo (SCT). This construct is defined by behavioral symptoms including, hypoactivity and daydreaming, and has been linked to increased internalizing behaviors. The current study examined if similar findings are displayed in children with prenatal alcohol exposure. Methods As part of a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 41 publications
4
35
1
1
Order By: Relevance
“…These findings are consistent with prior studies showing an exacerbated effect of multiple risk factors in the AE+ group, resulting in more severe deficits in parent-reported behavior (Glass, Graham, et al, 2013; Graham, Crocker, et al, 2013; Ware et al, 2013) but not in neuropsychological performance (Glass, Ware, et al, 2013; Rasmussen et al, 2010). Our results support and extend these previous findings, as this is the first study to compare this pattern within the same domain.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with prior studies showing an exacerbated effect of multiple risk factors in the AE+ group, resulting in more severe deficits in parent-reported behavior (Glass, Graham, et al, 2013; Graham, Crocker, et al, 2013; Ware et al, 2013) but not in neuropsychological performance (Glass, Ware, et al, 2013; Rasmussen et al, 2010). Our results support and extend these previous findings, as this is the first study to compare this pattern within the same domain.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, although parents were the source for most of the information on ADHD symptoms, the DISC interview includes questions about whether symptoms are present in more than one setting, as required for a diagnosis (American Psychiatric Association, 2013). In the AE group, 29 (85.3%) of subjects met these criteria for ADHD, consistent with previous literature (e.g., Burd et al, 2003, Graham et al, 2013, Ware et al, 2013). Children in the CON group had no indicators of ADHD, as defined above, nor did they have subclinical symptoms of ADHD on the C-DISC-4.0 (presence of 3–5 symptoms within a domain).…”
Section: Methodssupporting
confidence: 89%
“…The largest difference in problem scores between PAE and control groups was observed in 2 studies in which children in the PAE group were selected based on high levels of PAE (>4 alcoholic drinks at least once per week, or ≥13 drinks per week throughout pregnancy). 26,34 Levels of PAE were not defined or reported in Brown et al 24 Pooled effects for the 3 summary problem scales showed no statistically significant differences between groups (P > .05; Fig 4). Age group comparisons were not possible.…”
Section: Cbcl (6-18 Y 2001)mentioning
confidence: 99%
“…Four North American studies assessed predominantly African American (83%-94%) 24,30 or exclusively African American cohorts. 32,33 In addition to PAE/FASD groups, 3 studies included subgroups with attention-deficit/hyperactivity disorder (ADHD), 15,26,34 and 1 study included a subgroup with prenatal cocaine exposure (Supplemental Appendix 2). 33 Additional data (eg, individual group sample size data) were requested for 3 articles, 17,23,29 but authors were unable to access archives (n = 2) or did not respond (n = 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation